THE IMPACT OF PERCEIVED VALUE AND SERVICE QUALITY ON CUSTOMER SATISFACTION AND INTENTION TO USE APPLICATION-BASED TRANSPORTATION - Mirabel Winasis; Jacquelinda Sandra Sembel (Universitas Pelita Harapan, 2023)
Competition in mobile-based transportation increases sharply with the many new application-based transportation providers joining the competition. To win the competition, application-based transportation providers need to find strategies to improve consumers’ intention to use their applications. This study aims to examine the impact of Perceived Value and Service Quality on Customer Behavior and Intention to Use and Online Transportation in Jakarta and its surrounding areas. This study is a quantitative study using an online survey questionnaire distributed to 190 respondents in Jakarta and its surrounding areas. This study employs Structural Equation Modeling - Partial Least Square (SEM-PLS) using SmartPLS 3.3.2 for data analysis. According to the findings of the study, perceived value positively influences customer satisfaction and intention to use mobile application-based transportation. The finding also reveals that service quality has a positive influence on customer satisfaction but has no positive influence on behavioral intention. Thus, this study empirically underscores the importance of customer satisfaction in influencing the intention to use application-based transportation. It is then recommended that mobile-based transportation companies continuously improve customer satisfaction through perceived values and service quality.